Specific Learning Disorders: Variation Analysis of 15 Candidate Genes in 9 Multiplex Families - Calì, Francesco; Di Blasi, Francesco Domenico; Avola, Emanuela; Vinci, Mirella; Musumeci, Antonino; Gloria, Angelo; Greco, Donatella; Raciti, Daniela Rita; Zagami, Alessandro; Rizzo, Biagio; Città, Santina; Federico, Concetta; et al. (Medicina (Kaunas, Lithuania), 2023)
Background and Objectives: Specific Learning Disorder (SLD) is a complex neurobiological disorder characterized by a persistent difficult in reading (dyslexia), written expression (dysgraphia), and mathematics (dyscalculia). The hereditary and genetic component is one of the underlying causes of SLD, but the relationship between genes and the environment should be considered. Several genetic studies were performed in different populations to identify causative genes. Materials and Methods: Here, we show the analysis of 9 multiplex families with at least 2 individuals diagnosed with SLD per family, with a total of 37 persons, 21 of whom are young subjects with SLD, by means of Next-Generation Sequencing (NGS) to identify possible causative mutations in a panel of 15 candidate genes: CCPG1, CYP19A1, DCDC2, DGKI, DIP2A, DYM, GCFC2, KIAA0319, MC5R, MRPL19, NEDD4L, PCNT, PRMT2, ROBO1, and S100B. Results: We detected, in eight families out nine, SNP variants in the DGKI, DIP2A, KIAA0319, and PCNT genes, even if in silico analysis did not show any causative effect on this behavioral condition. In all cases, the mutation was transmitted by one of the two parents, thus excluding the case of de novo mutation. Moreover, the parent carrying the allelic variant transmitted to the children, in six out of seven families, reports language difficulties. Conclusions: Although the present results cannot be considered conclusive due to the limited sample size, the identification of genetic variants in the above genes can provide input for further research on the same, as well as on other genes/mutations, to better understand the genetic basis of this disorder, and from this perspective, to better understand also the neuropsychological and social aspects connected to this disorder, which affects an increasing number of young people.